(3GdeLdS Gdbhei ddeQCI hOhQg ai GdfghV HGdeQCI GdYGedI (B/ s - (3gHg eMeO NGdO YHOGdMejOs; (3GMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jJdNU ehVhY gPg GdQSGdI ai OQGSI OhQ GdeLdS Gdbhei ddeQCI ai GdfghV HGdeQCI GdYGedI HGYJHGQg GdeDSSI GdhWfjI GdJi GSJMOKJ dJfejI TFhf GdeQCI (B: (3hPdc ef NdGd aUhd GQHYI (B: (3hbO GSJYQV GdaUd GdGhd GdGMcGe GdeJYdbI HGdeQCI GdYGedI ai eYGjjQ GdYed GdOhdjI HGYJHGQgG GdGMcGe GdfehPLjI (B: (3GdJi jfHZi ddJTQjYGJ GdhWfjI GdeJYdbI HGdeQCI GdYGedIs
(3jTJed Ydi edGMb(B: 214-218s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B219-233s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdeLdS Gdbhei ddeQCIs; (3GdeQCI GdYGedIs; (3bGfhf GdYed GdeUQis; (3GdeSGhGIs; (3GdJejjRs; (3eSJhjGJ GdYeds; (3GdJOGHjQ GdMeGFjIs; (3JTZjd GdfSGAs; (3Shb GdYeds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs